NEUTRALISING ANTIBODIES TO INTERFERON–BETA PREDICT CONVERSION TO SECONDARY PROGRESSIVE MULTIPLE SCLEROSIS IN PATIENTS WITH MULTIPLE SCLEROSIS. Issue 11 (9th October 2013) - Gafson, Arie; Worthington, Viki; Lakdawala, Neghat; Giovannoni, Gavin; Farrell, Rachel
Abstract : Background: Multiple Sclerosis (MS) is the most common non–traumatic cause of acquired neurological disability in young people. Interferon–Beta (IFNβ) is a safe and well–tolerated first–line treatment for patients with MS (PwMS) in the relapsing–remitting phase of the disease (RRMS) and has been shown to reduce relapse rates by an average of 30% (Compston and Coles 2002). Neutralising antibodies (NAbs) are known to occur in approximately 25% of patients and in high titres reduce or eliminate the bioactivity of the drug [Pachner (Insight study) 2009, Farrell 2011]. Nabs are more likely to occur with high dose high frequency compounds–IFNβ 1a and IFNβ 1b (MS Study group 1996). Increased relapse rates and MRI activity have been described in patients with NAbs however effect on disability progression has been ambivalent [MS Study group 1996, Francis 2005, Kappos 2005, Farrell 2008]. Despite the existence of clinical guidelines recommending routine NAb testing with a view to switching therapy in those with persistent positive NAbs, uptake in the UK has been low [Polman 2010]. Objective: To assess the effect on disability in a UK cohort of patient attending the National Hospital for Neurology and Neurosurgery, London. Methods: A historical sample library of sera from PwMS treated with IFNβ was utilised. Subjects were eligible if they had a diagnosis of RRMS (Poser/McDonald) and had been treated for a minimum of 3–6 years. Serial samples were tested using the luciferase NAb assay (Farrell 2011) for the presence of NAbs and medical records reviewed to determine the clinical disease state at each time point (RRMS vs SPMS). Results: 112 subjects were identified, 53 remained RRMS up to at least the date of their last available sample and 59 patients had converted to secondary–progressive MS (SPMS) whilst on IFNβ or at a time point after the date of their last sample. Within the RRMS cohort (n=53), 4 were persistently positive at 2 years (7.5 %). Within the RRMS–SPMS cohort (n=59), 20 were persistently NAb positive at 2 years (34%). A positive NAb status at 24 months conferred a 4.25 fold increase in relative odds of progression to SPMS (95% CI: 1.53 to 11.84, p=0.006) using a logistic regression analysis. A sub–group analysis separating patients into high NAb titres (>400 neutralising units (NU)), low NAb titres (<100 NU) and negative titres (<20 NU) did not reveal a titre–dependent associated increase in risk of progression to SPMS (p>0.05). Conclusion: This study demonstrates a significantly increased risk of progression from RRMS to SPMS in patients who become NAb positive. As no current disease modifying treatments are effective in this phase of the disease patients at risk should be detected early and routine NAb testing can help to inform this decision.